What is Cultural Science? (And what it is not.) - Potts, J.; Hartley, John (Cultural Science, 2014)
Hartley and Potts (2014) argue that cultural science represents a new theoretical and methodological approach to the study of cultural structure, dynamics and use. We explain how this differs from the extant analytic frameworks of cultural studies, both as a research program and as a policy platform. The central idea is to reconceptualize what culture is, through a reinterpretation of what culture does. We argue that the semiotic productivity of culture makes groups – which we call demes – and demes make knowledge (what we call the externalism hypothesis); and the interaction of demes makes newness – new knowledge. Cultural science, then, is a new model of the cultural processes involved in socio-economic evolution and innovation of knowledge-making demes. The paper is in three sections, the first on the exhaustion of cultural studies; the second on the emergence of cultural science; and the third on some implications for cultural policy – illustrated by reference to Matthew Arnold’s policy on language preservation.